Fracasso escolar: um estudo sobre o sentido atribuído por estudantes da E.J.A. - Tomaz, Lucilene Macedo Balmant (2009)
This study sought to give voice to student E.J.A. focusing on subjective issues related to the meaning they attach to their past as students in early grades, as well as the factors and situations that contributed to the study leave. The research was conducted in a public school in Sao Paulo State in the outskirts of Itapevi city, with three students of the sport of Youth and Adults, being a student of 15 years of the 4th term of elementary school, a student of 60 years of 4 Termination of elementary school and another student of 22 years of the 3rd term of school. Was used in this research a qualitative approach, taking as a tool for data collection interview subsidized by a script. The analysis was performed according to the theoretical and methodological lined in socio-historical. The review process occurred through the agglutination of indicators resulting in the preparation of nuclei of meaning. Data analysis showed that the meaning attributed by the students of E.J.A. be based on several factors: the experiences of family education, facilities and difficulties in the teaching-learning process, one teacher and his way of work, friends and activities developed at school